Pengaruh Pengeluaran Pemerintah dan Upah Minimum terhadap Pertumbuhan Ekonomi di Provinsi Jambi - Fitri, Fadia Yuliza; Mailindra, Wiyan (Universitas Batanghari Jambi, 2024)
This research aims to measure the influence of government spending and minimum wages on the level of economic growth in Jambi Province. The method used is quantitative descriptive. The data used is secondary data in the form of a time series, namely data on government expenditure, minimum wages and economic growth for Jambi Province from 2014-2023 obtained from the Central Statistics Agency (BPS). The analytical tool used is multiple regression. The research results show that government spending and minimum wages do not have a significant effect on the level of economic growth in Jambi Province.